2020
DOI: 10.3389/fpsyt.2020.00095
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to Climate and Weather Changes in Euthymic Bipolar Subjects: Association With Suicide Attempts

Abstract: Background: Climate and weather are known to affect multiple areas of human life, including mental health. In bipolar disorder (BD), seasonality represents an environmental trigger for mood switches, and climatic variables may contribute to recurrences. Several studies reported seasonal and climatic-related variations in the rate of suicide attempts. Suicide risk is relevant in BD, with approximately 25% of patients attempting suicide. Therefore, this study aimed to assess sensitivity to weather and climatic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 70 publications
1
13
0
6
Order By: Relevance
“…Lastly, we found higher meteorosensitivity and meteoropathy intensity among the female participants in both age groups. This result is not only consistent with our final hypothesis, but also reflects other authors’ observations [ 11 , 26 ] for example, Connolly [ 10 ] showed that women are more prone to reacting to environmental factors, which relates especially to poor life satisfaction. Interestingly, low life satisfaction from several domains of functioning (e.g., job and health situation) is the worst on rainy days.…”
Section: Discussionsupporting
confidence: 93%
“…Lastly, we found higher meteorosensitivity and meteoropathy intensity among the female participants in both age groups. This result is not only consistent with our final hypothesis, but also reflects other authors’ observations [ 11 , 26 ] for example, Connolly [ 10 ] showed that women are more prone to reacting to environmental factors, which relates especially to poor life satisfaction. Interestingly, low life satisfaction from several domains of functioning (e.g., job and health situation) is the worst on rainy days.…”
Section: Discussionsupporting
confidence: 93%
“…Serotonin, involved in the functioning of the hypothalamic-pituitary-adrenal axis, can contribute to the development of two important meteoropathy components: anxiety and depression [32]. In a recent work, Di Nicola et al [47] indicated that meteorological factors such as sunlight or atmospheric pressure are associated with changes in the level of serotonin in the brain, which-in addition to dysfunction in the dopaminergic system-may be important for the process of emotion dysregulation. In…”
Section: Plos Onementioning
confidence: 99%
“…However, despite the relevance of climate change for this geographical area, there is little research specific to Italy or to the Mediterranean region on mental health and climate change (Aguglia et al, 2019 ; Di Giorgi, Michielin, & Michielin, 2020 ; Di Nicola et al, 2020 ; Oudin Åström et al, 2015 ; Preti, Lentini, & Maugeri, 2007 ; Rotgé, Fossati, & Lemogne, 2014 ). This is again in contrast with the attention given to physical health (Ministero della Salute, 2019 ; World Health Organization, 2018 ).…”
Section: Introductionmentioning
confidence: 99%